Supplementary reinoculation in topdressing of Rhizobium tropici in common bean crop: effects on nodulation, morphology, and grain yield - dos Santos Sousa, Westefann [UNESP] (2021)
Besides nitrogen fertilization (N), other processes constitute sources capable of supplying large amounts of N to plants, such as biological nitrogen fixation. In general, the inoculation technique exclusively in the seed, contributes on average up to 40% of the N acquired by the common bean crop. Another possible alternative, not widely used, is the reinoculation of the legume. The technique consists of reinoculation of the culture in areas that have already been inoculated at the time of sowing (inoculum in seed + inoculum in topdressing), also considered a supplementary inoculation. Thus, we believe the hypothesis that nitrogen fertilization, commonly used, could be partially or totally replaced by inoculation in seed, supplemented with inoculation in topdressing (reinoculation). The experiment was carried out in the 2019/2020 harvest, in the rainy season, in the experimental area belonging to the Goiás State University, Goiás, Brazil. The treatments consisted of two common bean cultivars, submitted to four methods of nitrogen supply: conventional, with the application of mineral N (60 kg ha-1); inoculation in seed + supplementary reinoculation in topdressing; inoculation exclusively in seed; inoculation exclusively in topdressing. The inoculation with Rhizobium tropici was efficient for increasing the number of nodules per plant, with results superior to the nitrogen fertilization of 20 and 40 kg ha−1 of N in the base and topdressing, respectively. Inoculation in seed combined with supplementary reinoculation in topdressing increases 2827 kg ha−1 in the grain yield of beans belonging to the BRS Valente cultivar, compared to the mineral nitrogen fertilization.